(untitled) (Research, Society and Development, 2022)
Introduction: Despite the large number of patients who have post-discharge survival from the Intensive Care Unit (ICU), most of them have complications that affect their functionality. Objective: To evaluate the functional profile of patients after discharge from the intensive care unit and to identify the determining factors that influence functionality. Methodology: Longitudinal, observational and descriptive study, with a quantitative approach, including patients admitted to the ICU of a University Hospital in the State of Sergipe, from August 2018 to March 2020. As a research instrument, the Functional Independence Measure was used (MIF) in three moments: at hospital admission, to measure functional independence prior to hospital admission; at ICU admission, to measure functionality prior to ICU admission; and on the immediate rise. Results: The sample consisted of 206 patients, including 91 participants. There was a reduction in FIM at ICU admission compared to previous hospital FIM and a tendency to increase at discharge, but the values do not return to what was observed before hospital admission. In addition, older patients who used mechanical ventilation for a longer period and with a longer hospital stay were determinant for FIM after discharge from the ICU. Conclusion: It is concluded that the hospitalization process, especially in the ICU, of older patients, using mechanical ventilation and with a longer hospital stay, causes a significant reduction in functionality.